Decoupled agendas under repression: social media and state media during COVID-19 in Iran - Kermani, Hossein; Bayat Makou, Alireza; Behzadian Nejad, Reza (Frontiers in Communication, 2025)
Despite a growing body of research on intermedia agenda-setting (IAS) in the contemporary hybrid media landscape, this line of inquiry remains mainly Western-centered. Furthermore, there is a lack of studies across different social platforms and between social media and official online media in authoritarian regimes. We combined computational, quantitative, qualitative, and discursive methods to address these gaps by investigating intermedia agenda-setting between three popular social media in Iran (Twitter, Telegram, and Instagram) and official news websites during the first wave of the COVID-19 pandemic. Our empirical analyses focused on four distinct datasets collected from January 27, 2020, to April 18, 2020. We find no significant influence between official and social media and no interplatform coupling among social networks, indicating platform-segmented agendas. While canonical health/news topics were common, contentious frames, notably Mismanagement and the politicization of hope and optimism, diverged sharply by platform. Taken together, these results show that in repressive settings, agenda cutting/suppression can decouple state and social spheres, and that user-base composition and platforms’ local trajectories, probably more than affordances or blocking alone, shape both intermedia and interplatform agenda independence. By providing a multi-platform, crisis-period map of agendas in Iran and demonstrating a directional test of influence under repression, the study refines IAS for non-democratic contexts and offers a transferable approach for comparative research on crisis communication.